Nanoleakage phenomenon on deproteinized human dentin - Patrícia de Britto Pereira Garcia Duarte; Eduardo Moreira da Silva (University of São Paulo, 2007)
OBJECTIVE: The purpose of this study was to evaluate the influence of dentin deproteinization on the nanoleakage phenomenon. MATERIAL AND METHODS: Class V cavities were prepared in 12 human molars with cervical margins located in dentin. The cavities were assigned to 2 groups (n=6) according to dentin treatment: Group I - dentin treated in accordance with the manufacturer's instructions and Group II - dentin treated following the manufacturer's instructions + 10% NaOCl. Each group was sub-divided into three groups, according to the DBS (dentin bonding system) used: Scotchbond Multi Purpose (SBMP), Prime & Bond NT (PB) and Clearfil SE Bond (SE), which were applied according to manufacturer's instructions. The cavities were restored with composite resin, and the specimens were immersed in a tracer agent (AgNO3 50%) for 24 h. The teeth were sectioned buccolingually through the center of the restorations, and nanoleakage pattern was evaluated by scanning electron microscopy (SEM) using the backscattered electron image mode. RESULTS: SEM analysis showed different nanoleakage patterns for each DBS. Irrespective of dentin treatments, all SBMP specimens showed nanoleakage. SE did not show any nanoleakage with both dentin treatments used. PB showed nanoleakage within the hybrid layer only in Group I. CONCLUSIONS: The influence of dentin deproteinization on the nanoleakage phenomenon was dependent on dentin bonding system formulation and bonding strategies.